Factors that affect the speaking performance of the students from levels II to V of the teens english program at CENIUES, year 2019 - Avilés Ruiz, Jacqueline Beatriz; Rodríguez Sánchez, Carmen Elizabeth; Gómez Magaña, Kevin Ernesto (2024)
This study aims at investigating the Factors that Affect the Speaking Performance of the Students from Levels II to V of the Teens English Program, at CENIUES, year 2019. This research project includes 8 chapters: Chapter I contains the delimitation of the problem, indicating the focus of the study, the description of the problem, and the research topics, questions and objectives, as well as a justification for these. Chapter II provides the theoretical framework with its historical background and previous research cited for the paper. Chapter III mentions the methodologies used to conduct the research, including approach, type of study and design. As well, it includes a population description, sampling frame, info about a pilot conducted and the instruments and analysis that was performed. Chapter IV analyses the data gathered through the conducted surveys after explaining the demographics where samples came from. Chapter V shows the findings of the research conducted and answers the questions formulated on Chapter I. Chapter VI contains conclusions on the analyzed data demonstrating what works based on a comparison of the teachers’ and students’ responses. Chapter VII provides professional recommendations to teachers and students to ensure improvement on students speaking performance. Chapter VIII discloses the bibliography and webliography used. The research design is non-experimental and the type of study is qualitative. This is a descriptive research supported by bibliographical field research.